SYNTHESIS, CHARACTERIZATION AND IN VITRO ANTIMICROBIAL STUDIES ON (2Z)-2-(2-HYDROXY-3H-INDOL-3-YLIDINEHYDRZINE-1- CARBOTHIOAMIDE AND ITS MANGANESE(II) AND IRON(II) COMPLEXES - ISYAKU S.; BELLO J; ALIYU H.N; ATIKU I., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Manganese (II) and Iron (II), complexes of a Schiff base obtained from condensation of Isatin and Thiosemicarbazide were synthesized. The Schiff base and the complexes were characterized by FTIR, magnetic susceptibility, molar conductance, AAS, solubility tests and melting point/decomposition temperature. The complexes showed moderate values of decomposition temperatures. Infrared spectral data of the Schiff base and the complexes, indicated coordination of the Schiff bases to the metal (II) ion via azomethine nitrogen, indole oxygen and thione sulphur. The effective magnetic moment of the complexes suggested an octahedral geometry. The molar conductivities of the complexes were 45.8 Ω-1cm2mol-1 and 11.7Ω-1cm2mol-1 which indicated the non-electrolytic nature of the complexes. The results of the absorbance and the empirical formula indicated that, the Schiff base is monobasic and tridentate in nature towards the metal ions. Both the ligand and the complexes were screened for antimicrobial activity against Staphylococcus aureus, Salmonella typhimurium, Escherichia coli (bacteria); Aspergillus flavus, Aspergillus fumigatus and Mucor species (fungi). Amoxicillin and Ketoconazole were used as positive control for the bacteria and fungi isolates respectively. The results showed that the complexes are more active than the free ligand but less active when compared with the standards.